Calcium sulfate hemihydrate composite material with antibacterial property as well as preparation method and application of calcium sulfate hemihydrate composite material in bone repair

By in-situ encapsulating phthalocyanine polymers on the surface of calcium sulfate hemihydrate, combined with photodynamic and photothermal therapy, the problems of hygroscopicity and antibiotic resistance of calcium sulfate hemihydrate were solved, achieving efficient bone repair and antibacterial effects, and improving the plasticity and biocompatibility of the material.

CN121401485APending Publication Date: 2026-01-27SHANDONG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511305935.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-12
Publication Date
2026-01-27

AI Technical Summary

Technical Problem

Existing calcium sulfate hemihydrate materials are prone to moisture absorption during bone repair, leading to unstable performance. Furthermore, they are susceptible to antibiotic resistance when used to treat bone infections, making it difficult to effectively control bacterial infections.

Method used

By in-situ encapsulating phthalocyanine polymers on the surface of calcium sulfate hemihydrate, a composite material with photodynamic and photothermal antibacterial properties is formed. The synergistic effect of photodynamic and photothermal therapy, combined with the tissue scaffold function of the polymer, improves the bone repair effect.

Benefits of technology

It achieves non-invasive or minimally invasive antibacterial treatment, avoids antibiotic resistance and toxic side effects, improves the success rate and survival rate of bone repair, and enhances the plasticity and biocompatibility of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005594258970000031
    Figure BDA0005594258970000031
  • Figure BDA0005594258970000032
    Figure BDA0005594258970000032
  • Figure FDA0005594258960000011
    Figure FDA0005594258960000011
Patent Text Reader

Abstract

The invention provides a calcium sulfate hemihydrate composite material with an antibacterial property, a preparation method of the calcium sulfate hemihydrate composite material and application of the calcium sulfate hemihydrate composite material in antibacterial bone repair. The preparation method comprises the following steps: firstly, selecting a polymer with good biocompatibility to be crosslinked with phthalocyanine, and then coating the surface of calcium sulfate hemihydrate with a phthalocyanine-polymer in a coordination manner through an in-situ synthesis method, so as to synthesize the calcium sulfate hemihydrate osteogenic material with uniform micron-sized granularity. According to the phthalocyanine-polymer-calcium sulfate hemihydrate composite material disclosed by the invention, the problems of drug resistance and toxic and side effects of antibiotics are solved through photodynamic and photo-thermal combined antibacterial properties; the defects that calcium sulfate hemihydrate is easy to absorb moisture and cannot ensure the bone repair performance are avoided through polymer coating; through the tissue scaffold effect of the polymer, adhesion and proliferation of new bone cells are facilitated, and the bone repair survival rate is greatly increased; moreover, through an in-situ synthesis method, the granularity of the calcium sulfate hemihydrate is effectively controlled, and the plasticity of the bone cement is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a hemihydrate calcium sulfate composite material with antibacterial properties, its preparation method, and its application in bone repair, belonging to the field of functional materials. Background Technology

[0002] Trauma, infection, tumors, and other diseases can all cause bone defects, a significant and long-standing threat to human health. When the bone defect exceeds the body's regenerative capacity, the body loses its self-healing ability, necessitating bone repair surgery. Therefore, selecting appropriate bone repair materials is crucial. Calcium sulfate hemihydrate is a common inorganic bone repair material. When mixed with water, it quickly becomes a malleable bone cement that can fill bone defects of various shapes. It then rapidly forms calcium sulfate dihydrate, which possesses high mechanical strength and a porous structure, providing both good support and osteoconductivity. However, the hygroscopic nature of calcium sulfate hemihydrate causes it to absorb moisture from the environment, altering its physical and chemical properties and causing it to agglomerate, affecting subsequent bone repair performance. Furthermore, the particle size of calcium sulfate hemihydrate affects its specific surface area, thus determining the malleability of the bone cement. Therefore, surface modification of calcium sulfate hemihydrate is an effective means of controlling its particle size and hygroscopicity to ensure its bone repair performance. Surface coating with polymeric materials or other inorganic substances is one of the effective methods for modifying calcium sulfate hemihydrate.

[0003] Following bone defect repair surgery, bacterial infection of the wound is a critical factor determining the success of bone repair. Infection can easily lead to bone implant failure, and in severe cases, even death. Although antibiotics remain the most commonly used antibacterial strategy, bacterial resistance is an urgent issue. Besides inherent resistance, the toxic side effects of antibiotics themselves are a major reason limiting their long-term use. Currently, there are precedents for using antibiotics loaded onto calcium sulfate hemihydrate to address bacterial infections during bone repair. However, frequent or excessive use of antibiotics can lead to bacterial resistance, leaving resistant strains that are more difficult to eradicate. Furthermore, due to the unique structure of bone tissue, oral and injected antibiotics have difficulty reaching the infection site, making treatment more challenging. Despite rapid advancements in medicine and the pharmaceutical industry, implant-related infections remain a serious challenge threatening human health. Therefore, the development and application of novel antibacterial bone repair materials are of great significance for reducing bacterial resistance, improving the antibacterial efficacy of drugs, and increasing the success rate of bone repair surgery.

[0004] Photodynamic therapy (PDT) and photothermal therapy (PTT) are two novel, non-antibiotic-dependent antibacterial strategies developed to address bacterial resistance. PDT involves a photosensitizer generating singlet oxygen under specific wavelengths of light, disrupting key bacterial structures such as cell membranes, proteins, and DNA, thus achieving an antibacterial effect. PPT involves a photothermal agent absorbing light energy and converting it into localized high heat, disrupting bacterial cell membranes, inducing protein denaturation, and damaging DNA. Combining PDT and PPT can achieve more effective antibacterial results. Unlike antibiotics, both PDT and PPT are non-invasive or minimally invasive, do not induce resistance, can be repeated, have few side effects, and minimal impact on normal cells and tissues. Therefore, whether used alone or in combination, PDT / PTT offer significant advantages in antibacterial treatment. Furthermore, the two treatment methods complement each other, creating a synergistic effect ("1+1>2"). Among numerous photosensitizers and photothermal agents, phthalocyanine and its derivatives have become a research hotspot in this field due to their low toxicity and simultaneous photodynamic and photothermal properties.

[0005] Therefore, developing calcium sulfate hemihydrate bone repair materials with in-situ photodynamic and photothermal antibacterial properties is a novel approach to overcome antibiotic resistance and toxic side effects, and to improve bone repair performance, which is of great significance. Summary of the Invention

[0006] To address the shortcomings of existing technologies, this invention provides a calcium sulfate hemihydrate composite material with in-situ antibacterial properties, its preparation method, and its application in antibacterial bone repair. First, this invention selects a polymer with good biocompatibility and crosslinks it with phthalocyanine. Then, through an in-situ synthesis method, phthalocyanine-polymer is coordinated and coated onto the surface of calcium sulfate hemihydrate, synthesizing a calcium sulfate hemihydrate osteogenic material with uniform micron-sized particles. By utilizing the photothermal / photodynamic antibacterial properties of phthalocyanine, the osteogenic properties of calcium sulfate hemihydrate, and the tissue scaffold function of the polymer, a novel multifunctional bone repair material with both osteogenic and in-situ antibacterial properties is provided.

[0007] The phthalocyanine-polymer-calcium sulfate hemihydrate composite material of the present invention solves the problems of antibiotic resistance and toxic side effects through the combined antibacterial properties of photodynamic and photothermal methods; the polymer coating avoids the disadvantages of calcium sulfate hemihydrate being hygroscopic and unable to guarantee bone repair performance; the polymer acts as a tissue scaffold, which is conducive to the adhesion and proliferation of new bone cells, greatly improving the survival rate of bone repair; and the in-situ synthesis method effectively controls the particle size of calcium sulfate hemihydrate, ensuring the plasticity of bone cement.

[0008] The technical solution of the present invention is as follows:

[0009] A method for preparing a calcium sulfate hemihydrate composite material with antibacterial properties includes the following steps:

[0010] (1) The carboxyl-containing polymer was fully dispersed in a mixed solution of deionized water and N,N-dimethylformamide; then 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, N-hydroxysuccinimide, N,N-diisopropylethylamine and aminosilyl phthalocyanine were added, and after reaction, the mixture was separated, purified and freeze-dried to obtain aminosilyl phthalocyanine-polymer;

[0011] (2) The amino-silicon phthalocyanine polymer was dissolved in anhydrous methanol, and anhydrous calcium carbonate and dilute sulfuric acid were added. After reaction, solid-liquid separation and drying were performed to obtain a hemihydrate calcium sulfate composite material with antibacterial properties.

[0012] According to the present invention, preferably, in step (1), the carboxyl-containing polymer is polyacrylic acid, polymethacrylic acid or polyglutamic acid; preferably, the carboxyl-containing polymer is polyacrylic acid, and the weight-average molecular weight of polyacrylic acid is 4000-6000.

[0013] According to the present invention, preferably, in step (1), the volume ratio of deionized water to N,N-dimethylformamide is 1 to 3:1, more preferably 1 to 2:1; the mass ratio of the carboxyl-containing polymer to the volume ratio of the mixed solution of deionized water and N,N-dimethylformamide is 0.05-1 g / L.

[0014] According to the present invention, in step (1), the aminosilylphthalocyanine has the following structure:

[0015]

[0016] Wherein, the R group is an alkyl, alkoxy, olefinic, or aromatic group, preferably an alkoxy group.

[0017] Preferably, the aminosilylphthalocyanine has the following structure:

[0018]

[0019] Where n = 0 to 10; more preferably, n = 1 to 4.

[0020] According to the present invention, the preparation method of the aminosilylphthalocyanine is prior art and can be obtained by referring to patent document CN111166882A.

[0021] According to the present invention, preferably, in step (1), the mass ratio of the carboxyl-containing polymer and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride is 1:1-2; the molar ratio of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to N-hydroxysuccinimide is 1:1; the molar ratio of N,N-diisopropylethylamine to aminosilyl phthalocyanine is 1-20:1, preferably 16-17:1; and the mass ratio of the carboxyl-containing polymer to aminosilyl phthalocyanine is 0.1-6:1, preferably 0.5-3:1.

[0022] According to the present invention, preferably, in step (1), the reaction temperature is room temperature, the reaction time is 2 to 5 days, and the reaction is carried out under stirring and a protective gas atmosphere. Preferably, the protective gas is nitrogen or argon.

[0023] According to the present invention, preferably, in step (1), the separation and purification method is as follows: the reaction product is placed in a dialysis bag, dialyzed in N,N-dimethylformamide until the dialysate becomes colorless, and then dialyzed with ultrapure water for 1 to 3 days.

[0024] According to the present invention, preferably, in step (2), the mass ratio of the aminosilyl phthalocyanine polymer to the volume ratio of anhydrous methanol is 0.5-1 g / L.

[0025] According to the present invention, preferably, in step (2), the mass ratio of anhydrous calcium carbonate to aminosilyl phthalocyanine polymer is 0.5 to 2:1; the volume ratio of anhydrous methanol to dilute sulfuric acid is 80 to 150:1; and the dilute sulfuric acid is a sulfuric acid aqueous solution with a concentration of 0.5-5 mol / L.

[0026] According to the present invention, preferably, in step (2), the reaction temperature is room temperature, the reaction time is 5-10 h, and the reaction is carried out under stirring conditions.

[0027] A calcium sulfate hemihydrate composite material with antibacterial properties is prepared by the above method. The composite material consists of calcium sulfate hemihydrate electrostatically coated with an amino-based silicon phthalocyanine polymer, wherein calcium ions on the surface of the calcium sulfate hemihydrate form coordination bonds with the carboxyl groups of the silicon phthalocyanine polymer; the amino-based silicon phthalocyanine polymer is prepared by an amide reaction between amino-based silicon phthalocyanine and a carboxyl-containing polymer.

[0028] The hemihydrate calcium sulfate composite material with antibacterial properties described in this invention can not only generate singlet oxygen, but also has good photothermal response. It is a composite material that has the synergistic antibacterial effect of photodynamic therapy and photothermal therapy in bone repair treatment.

[0029] The above-mentioned antibacterial calcium sulfate hemihydrate composite material is used in the preparation of antibacterial drugs and / or antibacterial bone repair drugs.

[0030] According to a preferred embodiment of the present invention, the composite material is used in the preparation of antibacterial drugs and / or antibacterial bone repair drugs for synergistic photodynamic therapy and photothermal therapy.

[0031] A pharmaceutical composition comprising the present invention’s antibacterial calcium sulfate hemihydrate composite material, and pharmaceutically acceptable excipients and / or carriers.

[0032] The technical features and beneficial effects of this invention are as follows:

[0033] 1. This invention first selects a polymer with good biocompatibility to crosslink with phthalocyanine, and then synthesizes a calcium sulfate hemihydrate osteogenic material with uniform micron-sized particles by in-situ synthesis of phthalocyanine-polymer on the surface of calcium sulfate hemihydrate. The phthalocyanine-polymer-calcium sulfate hemihydrate composite material of this invention is a novel bone repair material with in-situ antibacterial properties. It can perform bone repair while also possessing combined photodynamic and photothermal antibacterial properties, making it a novel multifunctional material for addressing antibiotic resistance and post-bone repair infections, with enormous application potential.

[0034] 2. This invention utilizes a combination of photodynamic and photothermal antibacterial methods, offering advantages such as being non-invasive or minimally invasive, not inducing drug resistance, allowing for repeated treatment, having few toxic side effects, and minimal impact on normal cells and tissues. It overcomes the disadvantages of antibiotic resistance and significant toxic side effects, while avoiding damage to human organs such as the liver and kidneys, and exhibits good biocompatibility.

[0035] 3. The phthalocyanine-polymer-calcium sulfate hemihydrate composite material of the present invention has good absorption and near-infrared photothermal conversion efficiency in the near-infrared field, high tissue penetration, and belongs to the optimal treatment window (700-900nm) of the human body, thus falling within the scope of near-infrared photothermal therapy.

[0036] 4. This invention utilizes an in-situ method for generating calcium sulfate hemihydrate. Through in-situ coating, the particle size of the calcium sulfate hemihydrate material can be effectively controlled, ensuring the plasticity of the bone cement and avoiding the disadvantage of calcium sulfate hemihydrate's hygroscopicity. This not only ensures the bone repair properties of the composite material but also, through the tissue scaffold effect of the polymer, promotes the adhesion and proliferation of new bone cells, greatly improving the survival rate of bone repair.

[0037] 5. Compared to the simple physical mixing method of commercially available calcium sulfate hemihydrate and aminosilyl phthalocyanine polymer, the in-situ synthesis of the present invention utilizes the carboxyl groups of the phthalocyanine polymer to react with the exposed CaO on the surface of calcium sulfate hemihydrate. 2+ Coordination bonds are formed, ensuring that the phthalocyanine is exposed, thereby guaranteeing its photothermal and photodynamic antibacterial properties. In the method of this invention, if polyacrylic acid is not added, the phthalocyanine cannot be extracted from the methanol solution during the formation of calcium sulfate hemihydrate, resulting only in a white powder without phthalocyanine, which lacks photodynamic and photothermal effects.

[0038] 6. The photothermal and photodynamic combined therapeutic properties of the phthalocyanine-carboxyl-containing polymer-calcium sulfate hemihydrate of the present invention can also kill cancer cells and can be applied to bone repair in bone cancer and bone metastases, with a wider range of applications and application potential. Attached Figure Description

[0039] Figure 1 Scanning electron microscope (SEM) image of the phthalocyanine-polyacrylic acid-calcium sulfate hemihydrate composite material prepared in Example 1;

[0040] Figure 2 Fourier transform infrared spectra of the phthalocyanine-polyacrylic acid-calcium sulfate hemihydrate composite material prepared in Example 1 and the raw materials;

[0041] Figure 3 The UV-Vis absorption spectra of the phthalocyanine-polyacrylic acid-calcium sulfate hemihydrate composite material and the raw materials prepared in Example 1 in water;

[0042] Figure 4 The UV-Vis spectrum of the singlet oxygen in N,N-dimethylformamide for the phthalocyanine-polyacrylic acid-calcium sulfate hemihydrate composite material prepared in Example 1 is shown; the horizontal axis is wavelength (nm) and the vertical axis is absorption (arbitrary unit).

[0043] Figure 5 The UV-Vis spectrum of the composite material prepared in Example 2 in N,N-dimethylformamide was measured for singlet oxygen; the horizontal axis is wavelength (nm) and the vertical axis is absorption (arbitrary unit).

[0044] Figure 6 The UV-Vis spectrum of the composite material prepared in Comparative Example 1 in N,N-dimethylformamide was measured for singlet oxygen; the horizontal axis is wavelength (nm) and the vertical axis is absorption (arbitrary unit).

[0045] Figure 7 Photothermal performance test curves of the phthalocyanine-polyacrylic acid-calcium sulfate hemihydrate composite material prepared in Example 1 under 808nm laser irradiation.

[0046] Figure 8 Photothermal performance test curves of the phthalocyanine-polyacrylic acid-calcium sulfate hemihydrate composite material prepared in Example 2 under 808nm laser irradiation.

[0047] Figure 9 The photothermal performance test curve of the composite material prepared in Comparative Example 1 under 808nm laser irradiation.

[0048] Figure 10The antibacterial properties of the phthalocyanine-polyacrylic acid-calcium sulfate hemihydrate composite material prepared in Example 1 against Staphylococcus aureus; the horizontal axis is the concentration (μg / ml), and the vertical axis is the bacterial survival rate (%).

[0049] Figure 11 The antibacterial properties of the phthalocyanine-polyacrylic acid-calcium sulfate hemihydrate composite material prepared in Example 1 against Escherichia coli; the horizontal axis is the concentration (μg / ml), and the vertical axis is the bacterial survival rate (%).

[0050] Figure 12 This is a comparison of the alkaline phosphatase (ALP) staining results after culturing mouse embryonic osteoblasts with the phthalocyanine-polyacrylic acid-calcium sulfate hemihydrate composite material prepared in Example 1 (right) and the control group without the composite material (left). Detailed Implementation

[0051] The present invention will be further described below with reference to specific embodiments and accompanying drawings, but is not limited thereto.

[0052] All raw materials used in this invention are commercially available analytical grade reagents.

[0053] Example 1: Taking amine-silicon phthalocyanine with n=1 as an example, the preparation method of a hemihydrate calcium sulfate composite material with antibacterial properties is as follows:

[0054] (1) 21.6 mg of polyacrylic acid (PAA, Mw ~ 5000) was added to a mixed solution of 10 mL of N,N-dimethylformamide and 15 mL of water, and sonicated for 1 h. 38.4 mg (0.2 mmol) of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 23 mg (0.2 mmol) of N-hydroxysuccinimide, 175 μL (0.5 mmol) of N,N-diisopropylethylamine, and 22.5 mg (0.03 mmol) of aminosilyl phthalocyanine (n = 1) (SiPc) were added to the solution, and the mixture was stirred at room temperature and reacted under a nitrogen atmosphere for 3 days. The reaction product was placed in a dialysis bag and dialyzed against N,N-dimethylformamide until the dialysate became colorless. Then, it was dialyzed against ultrapure water for 3 days, and lyophilized to obtain the intermediate product (PAA-SiPc).

[0055] (2) Weigh 20 mg of the intermediate product and dissolve it in 30 mL of anhydrous methanol. Add 30 mg of calcium carbonate and 300 μL of 1 mol / L dilute sulfuric acid. Stir the mixture at room temperature for 7 h to obtain a blue suspension. After centrifugation, the suspension is dried under vacuum at 60 °C to obtain phthalocyanine-polyacrylic acid-calcium sulfate hemihydrate (SiPc-PAA-CSH).

[0056] SEM images of the obtained phthalocyanine-polyacrylic acid-calcium sulfate hemihydrate composite material are shown below. Figure 1 As shown. The material consists of rod-shaped microcrystals with a length of 2-5 μm.

[0057] The infrared spectrum of the obtained phthalocyanine-polyacrylic acid-calcium sulfate hemihydrate composite material is as follows: Figure 2 As shown, CSH represents calcium sulfate hemihydrate. The composite material exhibits the characteristic peaks of the raw materials. The intensity of the carboxyl peak decreases as the reaction proceeds, indicating that the carboxyl groups of polyacrylic acid are covalently bonded to the amino groups of aminosilyl phthalocyanine and to the Ca on the surface of calcium sulfate hemihydrate. 2+ They combine to form ionic bonds.

[0058] The UV-Vis absorption spectra of the obtained phthalocyanine-polyacrylic acid-calcium sulfate hemihydrate composite material and the raw material of equivalent concentration dispersed in water (25 μg / mL) are as follows: Figure 3 As shown, the composite material exhibits good absorption in the red to near-infrared wavelength range.

[0059] Example 2: Taking aminosilyl phthalocyanine n=3 as an example

[0060] The preparation method of the antibacterial calcium sulfate hemihydrate composite material is as described in Example 1, except that in step (1), the aminosilyl phthalocyanine is replaced with an equimolar amount of aminosilyl phthalocyanine with n=3. Other steps and conditions are the same as in Example 1.

[0061] Comparative Example 1:

[0062] The preparation method of the composite material includes the following steps:

[0063] 21.6 mg of polyacrylic acid and 22.5 mg of aminosilyl phthalocyanine (n=1) were mixed evenly, and 20 mg was weighed and dissolved in 30 mL of anhydrous methanol. 30 mg of calcium carbonate and 300 μL of 1 mol / L dilute sulfuric acid were added, and the mixture was stirred at room temperature for 7 h to obtain a suspension. After centrifugation, the suspension was vacuum dried at 60 °C to obtain the composite material.

[0064] Test case

[0065] 1. Singlet oxygen (ROS) test

[0066] The ability of a sample to generate singlet oxygen was tested using 1,3-diphenylisobenzofuran (DPBF) as a quencher. A 150W halogen lamp equipped with a 610nm cutoff filter (λ>610nm) was used as the light source.

[0067] First, DPBF was prepared into a 40 μM N,N-dimethylformamide solution. Then, the sample was added to make the final concentration of the sample 10 μg / mL. The UV-Vis spectrum of the solution was then tested under light source irradiation.

[0068] The sample from Example 1 was tested, and the results are as follows: Figure 4 As shown.

[0069] The sample from Example 2 was tested, and the results are as follows: Figure 5 Show.

[0070] The test sample of Comparative Example 1 was tested, and the results are as follows: Figure 6 As shown.

[0071] The samples in Examples 1 and 2 showed good singlet oxygen generation ability. Comparative Example 1 was prepared by simple mixing, and phthalocyanine was still retained in methanol. The product did not contain phthalocyanine and could not generate singlet oxygen.

[0072] 2. Photothermal performance test

[0073] The composite material was prepared into dispersions of different concentrations using H2O, and then analyzed using an 808nm laser (2.5W / cm²). 2 Irradiation. Temperature changes over time were recorded using an infrared thermal imager.

[0074] The sample from Example 1 was tested, and the results are as follows: Figure 7 As shown.

[0075] The sample from Example 2 was tested, and the results are as follows: Figure 8 As shown.

[0076] The test sample of Comparative Example 1 was tested, and the results are as follows: Figure 9 As shown.

[0077] The results showed that the samples of Example 1 and Example 2 had good photothermal effects. The sample of Comparative Example 1 did not contain phthalocyanine and therefore did not have photothermal effects.

[0078] 3. In vitro antibacterial test

[0079] Staphylococcus aureus / Escherichia coli was prepared into a solution with a concentration of 10 using 0.85% NaCl solution. 5 Bacterial culture of 100 cells / mL was added to a 96-well plate and mixed with sample solutions of different concentrations. The solution was then analyzed using an 808nm (2.5W / cm) microscope. 2 Irradiate the bacteria sequentially with a pulsed laser (PTT) and a 660nm red LED (PDT) lamp for 5 minutes, or irradiate with an 808nm laser (PTT) lamp alone for 5 minutes, or irradiate with a red LED (PDT) lamp alone for 5 minutes. After irradiation, aspirate the bacterial culture and transfer it to BHI or LB solid medium. Incubate at 37°C for 24 hours, then count the bacterial colonies on the culture dishes. A control group without samples was also included.

[0080] The sample from Example 1 was tested, and the results are as follows: Figure 10 , Figure 11 As shown in the figure. The results indicate that PTT was the primary antibacterial treatment, and the combined effect of PDT and PTT was superior to either PTT or PDT alone, demonstrating the superior advantages of combination therapy.

[0081] 4. In vitro osteogenic experiment

[0082] Mouse embryonic osteoblasts (MC3T3) were seeded into 6-well cell culture plates (5 × 10⁻⁶ cells / well). 4 Cells were cultured in wells at 1000 cells / well until the cell confluence reached 70-80%. Then, osteogenic induction extract containing SiPc-PAA-CSH prepared in Example 1 was added, and the cells were cultured in a constant temperature incubator for 7 days (37°C, 5% CO2). Alkaline phosphatase (ALP) staining was performed using the BCIP / NBT alkaline phosphatase staining kit to evaluate the osteogenic capacity of the cells. The control group consisted of cells cultured in simple culture medium without SiPc-PAA-CSH osteogenic induction extract. The osteogenic test results are shown in the figure below. Figure 12 As shown.

[0083] The results showed that the phthalocyanine-polyacrylic acid-calcium sulfate hemihydrate composite material in Example 1 exhibited stronger color development compared to the control group, indicating that it has good osteogenic promoting ability.

Claims

1. A method for preparing a hemihydrate calcium sulfate composite material with antibacterial properties, comprising the following steps: (1) The carboxyl-containing polymer was fully dispersed in a mixed solution of deionized water and N,N-dimethylformamide; then 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, N-hydroxysuccinimide, N,N-diisopropylethylamine and aminosilyl phthalocyanine were added, and after reaction, the mixture was separated, purified and freeze-dried to obtain aminosilyl phthalocyanine-polymer; (2) The amino-silicon phthalocyanine polymer was dissolved in anhydrous methanol, and anhydrous calcium carbonate and dilute sulfuric acid were added. After reaction, solid-liquid separation and drying were performed to obtain a hemihydrate calcium sulfate composite material with antibacterial properties.

2. The method for preparing the antibacterial calcium sulfate hemihydrate composite material according to claim 1, characterized in that, In step (1), the carboxyl-containing polymer is polyacrylic acid, polymethacrylic acid, or polyglutamic acid; preferably, the carboxyl-containing polymer is polyacrylic acid, and the weight-average molecular weight of polyacrylic acid is 4000-6000.

3. The method for preparing the antibacterial calcium sulfate hemihydrate composite material according to claim 1, characterized in that, In step (1), the aminosilylphthalocyanine has the following structure: Wherein, the R group is an alkyl, alkoxy, olefinic, or aromatic group, preferably an alkoxy group.

4. The method for preparing the antibacterial calcium sulfate hemihydrate composite material according to claim 3, characterized in that, Aminosilylphthalocyanine has the following structure: Where n = 0 to 10; preferably, n = 1 to 4.

5. The method for preparing the antibacterial calcium sulfate hemihydrate composite material according to claim 1, characterized in that, Step (1) includes one or more of the following conditions: i. The volume ratio of deionized water to N,N-dimethylformamide is 1 to 3:1, preferably 1 to 2:1; the mass ratio of the carboxyl-containing polymer to the volume ratio of the mixed solution of deionized water and N,N-dimethylformamide is 0.05-1 g / L. ii. The mass ratio of the carboxyl-containing polymer and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride is 1:1-2; the molar ratio of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to N-hydroxysuccinimide is 1:1; the molar ratio of N,N-diisopropylethylamine to aminosilyl phthalocyanine is 1-20:1, preferably 16-17:1; the mass ratio of the carboxyl-containing polymer to aminosilyl phthalocyanine is 0.1-6:1, preferably 0.5-3:

1. iii. In step (1), the reaction temperature is room temperature, the reaction time is 2 to 5 days, and the reaction is carried out under stirring and protective gas atmosphere; preferably, the protective gas is nitrogen or argon.

6. The method for preparing the antibacterial calcium sulfate hemihydrate composite material according to claim 1, characterized in that, Step (2) includes one or more of the following conditions: i. The mass ratio of amino-silicon phthalocyanine-polymer to anhydrous methanol is 0.5-1 g / L; ii. The mass ratio of anhydrous calcium carbonate to aminosilyl phthalocyanine polymer is 0.5–2:1; the volume ratio of anhydrous methanol to dilute sulfuric acid is 80–150:1; the dilute sulfuric acid is a 0.5–5 mol / L sulfuric acid aqueous solution; iii. The reaction temperature is room temperature, the reaction time is 5-10 hours, and the reaction is carried out under stirring conditions.

7. A hemihydrate calcium sulfate composite material with antibacterial properties, characterized in that, It is prepared by the method described in any one of claims 1-6.

8. The use of the antibacterial calcium sulfate hemihydrate composite material as described in claim 7 in the preparation of antibacterial drugs and / or antibacterial bone repair drugs.

9. The application according to claim 8, characterized in that, The application of the composite material in the preparation of antibacterial drugs and / or antibacterial bone repair drugs for synergistic photodynamic therapy and photothermal therapy.

10. A pharmaceutical composition comprising the calcium sulfate hemihydrate composite material with antibacterial properties as described in claim 7, and pharmaceutically acceptable excipients and / or carriers.

Citation Information

Patent Citations

  • Phthalocyanine-RGD polypeptide-graphene oxide composite nano material and preparation method and application thereof

    CN111166882A